Enabling and Barriers of Implantable Contraceptive Use at Health Centre I North Denpasar - Nida Gustikawati; Luh Putu Lila Wulandari; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2014)
Background and purpose: The objective of this study was to explore the supporting and the inhibiting factors influencing the use of implant contraceptive use by women of childbearing age. Methods: The study was qualitative using a phenomenological approach. Data collection involved a purposively selected sample, conducting two FGD (10 implant users and 10 non-users) and 11 in-depth interviews among private midwives, government midwives, husbands, in-laws, and family planning staff. Results: FGD found that perceptions and attitudes towards implants of those already using the contraceptive were positive, while the perceptions and attitudes of non-users were less so. Some respondents intimated that they experienced side effects though these were not a deterring factor in usage. Enabling factors for the use of implant contraceptives were the availability and accessibility to the healthcare facilities and the support of their husbands. Access to facilities and infrastructure were not inhibiting factors either for the users or the non-users. Findings from in-depth interviews indicated that inhibiting factors included were the desire to have more children and the lack of promotion of the implant contraceptives. Healthcare provider informants stated that the lack of training was an inhibiting factor. Conclusion: Enabling factors for the use of implant contraceptives were the availability and accessibility to the healthcare facilities and the support of their husbands. Inhibiting factors were the desire to have more children, the lack of proper training for the health workers, as well as the lack of promotion of the implant contraceptive in the community